Urbanisation in developing countries : basic services and community participation - Mohanty, Bidyut (ed.) (New Delhi, 1993)
The rapid pace of urbanisation in the developing countries and the consequent pressure on urban civic amenities are matters of serious concern the world over. In this book experts, academicians, scholars and administra tors from Bangladesh, Brazil, Britain, China, France, India, Kenya, Mexico, Nepal and Sri Lanka grapple with the problems of ensuring for all urban residents, and specially the urban poor, access to adequate basic civic amenities in the burgeoning cities of developing countries. An important element in the debate is local community participation. Empowerment of urban communities through revitalization of local self government institutions is seen as critical in solving these aspects of urban crisis. This is the underlying argument of the authors writing in and about diverse national, socio-economic and cultural urban settings in this volume.
Keywords: Urban development-developing Countries